1997
DOI: 10.1212/wnl.48.2.306
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic tolerance in the brain

Abstract: Brief episodes of brain ischemia define a patient population at increased risk for stroke. These brief events (TIAs) warrant urgent evaluation and treatment. It is therefore counterintuitive that transient ischemia might induce tolerance and protect the brain from subsequent ischemia. However, accumulating data from studies on both myocardium and brain support such a concept. An understanding of the mechanisms involved in ischemic tolerance may define novel therapeutic strategies for brain protection.Ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
146
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(158 citation statements)
references
References 35 publications
10
146
1
1
Order By: Relevance
“…As mentioned above, HSP70 itself has been suggested to be involved in the neuroprotective effect of IPC (Kirino et al, 1991), and a number of studies, including this study, have shown that IPC induces the production of HSP70 in neurons (Chen et al, 1996;Chen and Simon, 1997). Prolonged cerebral ischemia up-regulates HSP70 in endothelial cells in normal rats and, to a reduced extent, IPC-treated rats, as shown in the current study and previous studies (Kinouchi et al, 1993a;Lindsberg et al, 1996).…”
Section: T Masada Et Al 30supporting
confidence: 83%
See 1 more Smart Citation
“…As mentioned above, HSP70 itself has been suggested to be involved in the neuroprotective effect of IPC (Kirino et al, 1991), and a number of studies, including this study, have shown that IPC induces the production of HSP70 in neurons (Chen et al, 1996;Chen and Simon, 1997). Prolonged cerebral ischemia up-regulates HSP70 in endothelial cells in normal rats and, to a reduced extent, IPC-treated rats, as shown in the current study and previous studies (Kinouchi et al, 1993a;Lindsberg et al, 1996).…”
Section: T Masada Et Al 30supporting
confidence: 83%
“…Many substances are produced after IPC through induction of gene expression (Chen and Simon, 1997); these include interleukin-1 receptor antagonist and free radical scavengers (Barone et al, 1998;Kato et al, 1995;Ohtsuki et al, 1996;Toyoda et al, 1997) that might reduce inflammation-and free radical-induced damage. Although these substances are involved in the parenchymal cell protective effect, they may also contribute to the cerebrovascular protective effect.…”
Section: T Masada Et Al 30mentioning
confidence: 99%
“…In addition, resistance to oxidative stressors could be mediated by other factors, including the redox-sensitive transcription factor NF-kB (65). Interestingly, a similar resistance phenomenon has been observed during ischemic pre-conditioning, a condition whereby neurons exposed to sublethal cerebral ischemia become resistant to a subsequent lethal ischemic insult (66). In this case, enhanced mitochondrial calcium sequestration and/or calcium efflux is thought to be an important compensatory mechanism (67).…”
Section: Discussionmentioning
confidence: 85%
“…At longer intervals (Ͼ4 hr), adenosine levels may be at least partially replenished. Even longer inter-episode intervals (24 hr) give rise to ischemic preconditioning (Chen and Simon, 1997) wherein neuropathology is reduced. Given the long delay before protective preconditioning is seen in vivo and the requirement for protein synthesis, the extent to which protective preconditioning can be studied in vitro, over the time course of the present experiments, is questionable.…”
Section: Implications For Neuroprotection By Adenosinementioning
confidence: 99%